Literary Post-editing and the Question of Copyright - Taivalkoski-Shilov Kristiina; Koponen Maarit (Denmark, 2025)
Translation poses a challenge to copyright laws, which extend protection to works based on the originality of expression rather than the ideas expressed, because translations convey the ideas of the original in a different language and therefore also use different expressions. Technologization of translation has further increased this complexity, as tools such as translation memories and machine translation and post-editing practices are starting to also emerge in literary translation, calling for a more detailed investigation of the literary post-editor’s role and ownership of the text. Post-editing of machine-translated output could give rise to copyright protection, but this depends on the level of intervention and whether the post-edited translation is deemed sufficiently original. This article aims to investigate questions of originality, creativity and textual ownership in literary post-editing. We examine two cases where a literary text was machine translated, post-edited and then published. Our research materials consist of the peritexts surrounding the published translations and three epitexts: one publisher’s website, a research article written by one of the post-editors to describe the experience, and an interview with the other post-editor. Through a qualitative content analysis of these materials, we examine how they reflect the post-editors’ approach to post-editing, personal input in the process and textual ownership of the post-edited target text. The findings suggest that the two post-editors have different approaches to post-editing, leading them to differing perceptions of their own creative input and relationship with the final text.